Minat Belajar Matematika Siswa Kelas XII TKJ Di SMK Pembina Bangsa Bukittinggi - Suci Febrianti; Aniswita Aniswita; Rio Fernandes (Universitas Pahlawan Tuanku Tambusai, 2022)
Student learning interest is a willingness or desire in students to learn something. When students have a high interest in learning mathematics they will study as best they can at school or at home, conversely if students lack a high interest in learning mathematics they are not enthusiastic about learning mathematics, this has implications for low learning outcomes in mathematics. The author describes the interest in learning mathematics in class XII TKJ students at the Pembina Bangsa Vocational School, Bukittinggi. The subjects used were 19 class XII TKJ students at Pembina Bangsa Vocational High School Bukittinggi and a math teacher for XII TKJ class at Pembina Bangsa Vocational High School Bukittinggi. Research data was collected using interviews and questionnaires. Questionnaire data on interest in learning mathematics in class XII TKJ students at the Pembina Bangsa Vocational High School Bukittinggi as a whole obtained a percentage of 90% which was classified as very high. Students enjoy learning mathematics, are actively involved when learning activities take place, feel interested in learning mathematics and focus when learning mathematics takes place. In the first indicator, namely students' enjoyment in learning mathematics, a percentage of 89% is classified as very high, in the second indicator, namely attention students when participating in mathematics learning obtain a percentage of 90% which is classified as very high, on the third indicator, namely student interest when learning mathematics obtains a percentage of 92% which is classified very high, and on the fourth indicator, namely student involvement when learning mathematics obtains a percentage of 90% which classified as very high. Keywords: Interest, Learning, Mathematics